Recommendations for Measurement of Bodybuilding Internal Training Load by eTRIMP Method - Fernandes, Haniel (Journal of Sports Medicine and Therapy, 2023)
Currently, analysis of training data metrics has become increasingly important in characterizing high throughput. In fact, in bodybuilding, the RPE (rate of perceived exertion) assessment is the metric commonly used to calculate training volume. Therefore, this study demonstrates another way for bodybuilding athletes to evaluate their training through heart rate using the TRIMP (training impulse) method proposed by Edwards to analyze the intensity of a given training model. For this athlete, it is important to stay most of the time outside heart rate zone 1, not have more than 10% of total training time in zone 5 and contain the largest proportion of total training time in zones 2, 3 and 4.